Proteomics in Domestic Animals: from Farm to Systems Biology (Springer International Publishing, 2018)
Proteomics, like other post-genomics tools, has been growing at a rapid pace and has important applications in numerous fields of science. While its use in animal and veterinary sciences is still limited, there have been considerable advances in this field in recent years, in areas as diverse as physiology, nutrition and food of animal origin processing. This is mainly as a consequence of a wider availability and better understanding of proteomics methodologies by animal and veterinary researchers. This book provides a comprehensive, state-of-the-art account of the status of farm-animal proteomics research, focusing on the principles behind proteomics methodologies and its specific applications and offering clear example.